Model Pembelajaran PAI Holistik-Digital dalam Membangun Motivasi Belajar Siswa SD - Muhamad Abdul Gofur; Nunu Kirani Lie (STAI Bani Saleh Bekasi, 2025)
This study aims to describe the strategies of Islamic Religious Education (PAI) teachers in enhancing the learning enthusiasm of fifth-grade students at SD Negeri Duren Jaya 01 Bekasi, identify supporting and inhibiting factors, and analyze the impacts, strengths, and weaknesses of these strategies. Employing a qualitative descriptive approach with a case study method, data were collected through participant observation, in-depth interviews with four PAI teachers, and comprehensive documentation studies. Data analysis followed the Miles, Huberman, and Saldana interactive model. The results reveal that PAI teachers' strategies encompass structured spiritual approaches (prayers, murojaah, moral messages), behavioral modeling (uswatun hasanah), interactive digital audiovisual-based learning methods, and humanistic emotional approaches. The success of these strategies is significantly influenced by internal factors (students' intrinsic motivation and readiness) and external factors (school facilities and parental support). This study offers the Adaptive Scaffolding-Based Implementation (ASBI) framework as a solution model to optimize PAI learning strategies in elementary schools.